Equity in transboundary water law: Valuable paradigm or merely semantics? - Lautze, Jonathan F.; Giordano, Mark (2006)
Equity has emerged as an important principle in transboundary water law in recent years, particularly in relation to water allocation. Yet basic questions remain unanswered. What constitutes an equitable transboundary water agreement? What constitutes an equitable allocation of shared waters? And has the inclusion of equitable language really made a difference in transboundary water law at the basin level? This paper uses Africa as a case study to critically assess past efforts to integrate equity into transboundary water law. The qualitative characteristics of agreements claiming to consider equity are first compared to those making no such assertion to reveal what differences, if any, exist. The paper then develops a quantitative methodology to measure equity in transboundary water allocations. This methodology is used to compare codified water allocations in agreements that purport to consider equity with those that do not. The findings reveal that agreements referring to equity differ substantively from others and, in fact, divide water in a more equitable manner. While the study is limited to Africa, it at least suggests that the equity concepts behind the 1966 Helsinki Rules and the 1997 United Nations Convention on Non-Navigational Uses of International Watercourses have had a tangible impact on basin level agreements.